O “bem estar bem” no discurso identitário das consultoras da Natura: análise de recepção da comunicação organizacional na sociedade do consumo - Araújo, Joana Lordelo Costa (2008)
If we consider that nowadays the relationship beetween consumers and objects have changed from utility aspect to the meaning of what we consume, the organizational discourse and its communication activities not only interferes in the product’s sales volume but also impacts socially. Then, organizations are more than players in the production system, they are symbolic construction, they mediate and define peculiars criterias to look into reality. Thefore, communication and organization emerge in the discourses encounters that show up social practices. Considering the organizations meanings, products and different communication activities, this research has the aim of explaining how Natura, a cosmetic brazilian company, is represented and how its image interact with consumption society ideas in order to participate in the identities construction of the outsourced sales force: the consultors. This paper analises two diferents communication texts that belong to the Natura magazine dedicated to its consultors. The main idea is to think how representations of organizations interact with the consumption society features and participate in the identities construction. Before starting, this research assumes that Natura’s consultors reproduce, in a certain way, the organization discourse, because the Natura communication shows a positive relationship between them. This paper proposes to understand this symbolic process. In this logic, the organizations would be sense producers and reproducers interacting in a unique way with the social memory helping to install the belonging feeling. To develop this study, this research uses the Bauman consumption society ideas, the Orlandi Discourse Analysis and Montreal School Organizational Communication theories.